2013
DOI: 10.1371/journal.pone.0070458
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Based Therapy Decreases Risks of Hepatocellular Carcinoma and Complications of Cirrhosis in Chronic Hepatitis C Patients

Abstract: BackgroundInterferon-based therapy (IBT) has been the standard of care for hepatitis C virus (HCV) infection. However, conflicting results exist regarding the effects of IBT on risk of developing hepatocellular carcinoma (HCC) and cirrhosis-associated complications, and most included highly selected patients.MethodsThis 8-year cohort study was based on the Longitudinal Health Insurance Database 2000 (LHID 2000) consisting of 1,000,000 beneficiaries randomly selected from all Taiwan National Health Insurance en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 37 publications
(48 reference statements)
1
31
0
Order By: Relevance
“…Therefore, HCV infection should no longer be considered as a disease concerning hepatologists alone -all physicians should improve their knowledge on HCV infection. Third, recent studies have confirmed that antiviral treatment of HCV infection can improve cardiovascular, renal, and hepatic outcomes in HCV-infected patients [28,29], indicating the potential for more optimistic outcomes of HCVassociated vascular complications. Accordingly, further research is warranted to elucidate the effects of antiviral treatment on PAD.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, HCV infection should no longer be considered as a disease concerning hepatologists alone -all physicians should improve their knowledge on HCV infection. Third, recent studies have confirmed that antiviral treatment of HCV infection can improve cardiovascular, renal, and hepatic outcomes in HCV-infected patients [28,29], indicating the potential for more optimistic outcomes of HCVassociated vascular complications. Accordingly, further research is warranted to elucidate the effects of antiviral treatment on PAD.…”
Section: Discussionmentioning
confidence: 95%
“…The NHIRD has been described in detail in previous studies. 18,19 In brief, the NHIRD contains the registration data of all people who have been beneficiaries of the NHI program, which covered 99% of Taiwan's population and approximately 22,600,000 people in 2007. The NHRI maintains the NHIRD and provides it to scientists in Taiwan for research purposes.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…The aims of antiviral therapy are to achieve virological cure; to prevent progression of liver disease and the occurrence of cirrhosis-related complications; to increase the quality of life and survival of patients; to remove the stigma associated with infection; and to prevent future transmission of the virus [8]. The accumulated data from interferon (IFN)-based treatments demonstrate a beneficent long-term clinical effect in patients who achieve SVR, by preventing the development of esophageal varices (EV), reducing the risk of HCC and the need for liver transplantation, and reducing liver-related mortality [2,[9][10][11][12]. The long-term histological regression of the grade of fibrosis was also documented, which reinforces the dynamic nature of fibrosis progression in the natural course of the disease [4,13,14].…”
Section: Introductionmentioning
confidence: 99%